Amiloride Analogs as ASIC1a Inhibitors. (18th February 2016) - Leng, Tian‐Dong; Si, Hong‐Fang; Li, Jun; Yang, Tao; Zhu, Mengyuan; Wang, Binghe; Simon, Roger P.; Xiong, Zhi‐Gang
Summary: Background: ASIC1a, the predominant acid‐sensing ion channels (ASICs), is implicated in neurological disorders including stroke, traumatic spinal cord injury, and ALS. Potent ASIC1a inhibitors should have promising therapeutic potential for ASIC1a‐related diseases. Aims: We examined the inhibitory effects of a number of amiloride analogs on ASIC1a currents, aimed at understanding the structure–activity relationship and identifying potent ASIC1a inhibitors for stroke intervention. Methods: Whole‐cell patch‐clamp techniques and a mouse model of middle cerebral artery occlusion (MCAO)‐induced focal ischemia were used. Surflex‐Dock was used to dock the analogs into the pocket with default parameters. Results: Amiloride and its analogs inhibit ASIC1a currents expressed in Chinese hamster ovary cells with a potency rank order of benzamil > phenamil > 5‐( N, N ‐dimethyl)amiloride (DMA) > amiloride > 5‐( N, N ‐hexamethylene)amiloride (HMA) ≥ 5‐( N ‐methyl‐ N ‐isopropyl)amiloride (MIA) > 5‐( N ‐ethyl‐ N ‐isopropyl)amiloride (EIPA). In addition, amiloride and its analogs inhibit ASIC currents in cortical neurons with the same potency rank order. In mice, benzamil and EIPA decreased MCAO‐induced infarct volume. Similar to its effect on the ASIC current, benzamil showed a much higher potency than EIPA. Conclusion: Addition of a benzyl group to the terminal guanidinyl group resulted in enhanced inhibitory activity on ASIC1a. On the other hand, the bulky groups added to the 5‐amino residues slightly decreased the activity. Among the tested amiloride analogs, benzamil is the most potent ASIC1a inhibitor.